Warrior ways : explorations in modern military folklore - Tuleja, Tad, 1944-; Eliason, Eric A. (Eric Alden), 1967- (Utah State University Press, 2012)
Warrior Ways is one of the first book-length explorations of military folklife, and focuses on the lore produced by modern American warriors, illuminating the ways in which members of the armed services creatively express the complex experience of military life. In short, lively essays, contributors to the volume, all of whom have close personal or professional relationships to the military, examine battlefield talismans, personal narrative (storytelling), "Jody calls" (marching and running cadences), slang, homophobia and transgressive humor, music, and photography, among other cultur.